2017
DOI: 10.3390/v9040068
|View full text |Cite
|
Sign up to set email alerts
|

ICAM-1 Binding Rhinoviruses Enter HeLa Cells via Multiple Pathways and Travel to Distinct Intracellular Compartments for Uncoating

Abstract: Of the more than 150 human rhinovirus (RV) serotypes, 89 utilize intercellular adhesion molecule-1 (ICAM-1) for cell entry. These belong either to species A or B. We recently demonstrated that RV-B14 and RV-A89, despite binding this same receptor, are routed into distinct endosomal compartments for release of their RNA into the cytosol. To gain insight into the underlying mechanism we now comparatively investigate the port of entry, temperature-dependence of uncoating, and intracellular routing of RV-B3, RV-B1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…For detection, secondary antibodies labeled with Alexa fluor (Life Technologies, Carlsbad, CA, USA) were used at 1 μg/mL, followed by extensive washing. The slides were mounted, and fluorescence microscopy images were recorded on a TissueFAXS automated microscope (TissueGnostics, Vienna, Austria) as in Ganjian et al [ 14 ]. The presence of PDS diminished the number of virus-positive cells in all cases by about 70% compared with cells identically infected with the respective untreated virus.…”
Section: Textmentioning
confidence: 99%
“…For detection, secondary antibodies labeled with Alexa fluor (Life Technologies, Carlsbad, CA, USA) were used at 1 μg/mL, followed by extensive washing. The slides were mounted, and fluorescence microscopy images were recorded on a TissueFAXS automated microscope (TissueGnostics, Vienna, Austria) as in Ganjian et al [ 14 ]. The presence of PDS diminished the number of virus-positive cells in all cases by about 70% compared with cells identically infected with the respective untreated virus.…”
Section: Textmentioning
confidence: 99%
“…Sometimes, the activation of penetration by alternative cues, such as low pH or proteolytic cleavage, depend on cell line or virus strain [37]. The pathway by which the virus negotiates the endocytic network in the cell may involve alternative routes and penetration compartments as shown by the rhinovirus example in Table 2 [79].…”
Section: Variation and Redundancymentioning
confidence: 99%
“…Serotypes that use ICAM-1 as receptor enter via clathrin-mediated endocytosis and micropinocytosis. Among these, members of the A serotype are routed for acid-activated uncoating in recycling endosomes and members of the B serotype in maturing endosomes [79].…”
Section: Rhinovirusesmentioning
confidence: 99%
“…In agreement with our study, dynein was shown to be important during cell entry of the murine PyV (40), although it is not known whether this motor acts to disassemble the virus. Beyond the PyV family, other viruses, including human immunodeficiency virus type 1 (41,42), influenza A virus (43), rhinoviruses (44), herpes simplex virus (45), and murine leukemia virus (46), exploit dynein's function to support some aspect of their entry processes. Thus, our study further underscores the concept that exploiting cellular motors is a common strategy used by viruses during infection.…”
mentioning
confidence: 99%